Meta-analysis of Clinical Outcomes Using Ceftazidime/Avibactam, Ceftolozane/Tazobactam, and Meropenem/Vaborbactam for the Treatment of Multidrug-Resistant Gram-Negative Infections. (5th January 2021) - Wilson, Geneva M; Fitzpatrick, Margaret; Walding, Kyle; Gonzalez, Beverly; Schweizer, Marin L; Suda, Katie J; Evans, Charlesnika T
Abstract: Ceftolozane-tazobactam (C/T), ceftazidime-avibactam (C/A), and meropenem/vaborbactam (M/V) are new beta-lactam/beta-lactamase combination antibiotics commonly used to treat multidrug-resistant Pseudomonas aeruginosa (MDRPA) and carbapenem-resistant Enterobacteriaceae (CRE) infections. This review reports the clinical success rates for C/T, C/A, and M/V. PubMed and EMBASE were searched from January 1, 2012, through September 2, 2020, for publications detailing the use of C/T, C/A, and M/V. A meta-analysis determined the pooled effectiveness of C/T, C/A, and M/V. The literature search returned 1950 publications; 29 publications representing 1620 patients were retained. Pneumonia was the predominant infection type (49.8%). MDRPA was the major pathogen treated (65.3%). The pooled clinical success rate was 73.3% (95% CI, 68.9%–77.5%). C/T, C/A, or M/V resistance was reported in 8.9% of the population. These antibiotics had a high clinical success rate in patients with complicated infections and limited treatment options. Larger studies comparing C/T, C/A, and M/V against other antibiotic regimens are needed.